KITAB SUCI DAN PENDIDIKAN NILAI - B.A. Pareira (Litbang STFT Widya Sasana Malang, 2001)
The demand of value education is evident today. In Indonesia value formation occupies the certain place in the whole of frame education. Teachers, particularly those of the young people, are so much concerned with problem of value especially that of life, ethical relationship, and politics. This article elaborates the topics from biblical point of view, i.e., from the Old Testament. As the author gets involved in priestly formation in biblical territory with specialization of the Old Testament, the article shall draw closely ideas of ethical formation from the Book of Proverbs and of Ecclesiastes. Both Proverbs and Ecclesiastes are dealing with value education